Dream Theories and Nuruddin Farah’s Dream Novel of Inversion - Carbonieri, Divanize (2012)
The aim of this paper is to establish a connection between dream studies and literature, analyzing how different dream theories influenced the reading and possibly the construction of three contemporary African novels. The object of analysis is the trilogy Blood in the sun by Somali writer Nuruddin Farah, in which the author proposes the combination of two narrative layers, one given by the characters’ experience in their vigil and another given by their dreams. The immobility experienced by them when they are fully awake, caused by the political and social oppression they face in their communities, is compensated in dream spaces, reversing what they experience in the real world. For the understanding of such works, in which dreams are not only appendages to narrative, but elements that intensely change the structure of the novels, it is necessary to extend the critical repertoire with the dialogue with multiple dream theories.